Bilateral hydronephrosis and hydroureter after ovariohysterectomy using nylon cable tie: a case report - Mesquita, L. R. [UNESP]; Rahal, S. C. [UNESP]; Matsubara, L. M. [UNESP]; Mamprim, M. J. [UNESP]; Foschini, C. R. [UNESP]; Faria, L. G. [UNESP]; Kano, W. T. [UNESP] (Czech Academy Agricultural Sciences, 2015)
A spayed crossbred female dog was presented due to progressive weight loss, emesis and anorexia over the preceding month. A complete blood count, urinalysis, serum biochemical panel, and ultrasound were initially performed. Computed tomography urography was performed as a complementary exam. Based on ultrasound and CT findings an exploratory celiotomy was performed to remove hyperdense structures that could be the cause of the hydronephrosis and hydroureter in both kidneys. An extensive granulomatous reaction was found near the caudal pole to the left kidney. A nylon cable tie adhering firmly to this tissue was removed during surgical excision. On the dorsal surface of the bladder an extensive granulomatous reaction that had entrapped the right ureter was also noted. Another nylon cable tie was removed and the ureter was released. Eight months postoperatively, the dog was in good general physical condition, showing appetite and vigour. Abdominal ultrasonography showed improvement of the hydronephrosis in both kidneys. The urea ratio was normal, but the creatinine level was slightly elevated, suggesting a guarded prognosis. Thus, bilateral hydronephrosis as observed in the present study should be considered as a major complication after elective ovariohysterectomy.
Keywords: Nylon cable tie; Renal injury; Surgery, computed tomography excretory; Dog